The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.3133/ofr77728
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the water resources of Death Valley, California-Nevada

Abstract: Water supplies in Death Valley National Monument and vicinity are limited to groundwater sources, almost without exception. Most streams in the desert area flow only ephemerally, typically during flash floods. Ground water supports perennial flow over a few short reaches of some streams. There are several hundred freshwater springs and seeps in the monument, but only a small percentage of these, including most of the large springs, are in areas of present or projected intensive use by man. Most springs are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 11 publications
1
49
2
Order By: Relevance
“…This method has been applied to more than 200 basins in Nevada and in other western states. Controversy over the limitations and accuracy of this method has existed for some time (Watson et al, 1976;Miller, 1977). However, more recent studies by Dettinger (1989) and Avon and Durbin (1992) have indicated that the Maxey and Eakin approach yields recharge estimates that are generally in good agreement with independent estimates.…”
Section: Introduction Previous Researchmentioning
confidence: 92%
“…This method has been applied to more than 200 basins in Nevada and in other western states. Controversy over the limitations and accuracy of this method has existed for some time (Watson et al, 1976;Miller, 1977). However, more recent studies by Dettinger (1989) and Avon and Durbin (1992) have indicated that the Maxey and Eakin approach yields recharge estimates that are generally in good agreement with independent estimates.…”
Section: Introduction Previous Researchmentioning
confidence: 92%
“…The Grapevine Mountains are underlain by intensely folded and faulted sedimentary rocks of Paleozoic age. In the central to northern part of the range, the sedimentary rocks are capped by volcanic basalts of Tertiary age (Miller, 1977).…”
Section: Geographic Settingmentioning
confidence: 99%
“…Throughout the study area, Precambrian igneous and metamorphic intrusive (basement) rocks form the cores of mountain ranges. These rocks are overlain by thick sections of Paleozoic sedimentary strata, Mesozoic and Cenozoic intrusive, extrusive, and clastic rock formations, and extensive accumulations of alluvial, colluvial, and eolian sediments (Miller, 1977;Bedinger and others, 1989). The ranges and intervening valleys in the study area are part of the complex horst-and-graben structural framework of the Basin and Range.…”
Section: Physiographic Settingmentioning
confidence: 99%